(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the parable as a genre. The relevance of turning to the parable is due to the fact that interest in the parable does not weaken, and each author, using the traditions of the genre, introduces something new, acting as an innovator. The first thing that attracts attention is the differences between the modern parable as a genre. Today there is no instructiveness and instructions in it. It does not give a ready answer, but makes you think about the proposed topic. The parable easily connects with other genres of literature, deepening their meaning. In modern fiction, the popularity of the parable as a genre makes those who turn to the parable think about its essence, boundaries, the possibilities of their expansion or, on the contrary, narrowing, about the ways of genre contamination and transformation. The breadth of the use of the name "parable" and the range of judgments about its possibilities are impressive.